PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR TENTANG TEKANAN ZAT PADAT - Elisabeth Elsa Andriani; Edy Tandililing; Syukran Mursyid (Universitas Tanjungpura, 2019)
AbstractThe aim of this research is to improve the student learning outcomes by guided inquiry learning models about solid pressure. The populations of this reseach is 8th grade of SMP Negeri 6 Pontianak’s students on 2018/2019 school year. Research sample is determined by purposive sampling technique consists of 29 students. The kind of this research is quasy experimental research used one group pretest posttest design. The datas took by test learning outcomes method consists of 9 multiple choice questions. The result of analisys in t-test shown that the student learning outcomes at points Sig. (2-tailed) 0,000 < 0,05 for t-test score. The results of this research, there is a significant difference between learning outcomes in the pretest and posttest data. The results of this research shown 44 for before while 66 for after being treated in average score of the student learning outcomes. Then the data is analyzed using N-gain testing 0,4 in the medium category, it means there is an improvement of the student learning outcomes about solid pressure after applied guided inquiry learning models. The result of this study are expected to be an alternative in efforts to improve the student learning outcomes about solid pressure.Keywords: Guided Inquiry, Learning Outcomes, Solid Pressure